CSF-resident CD4+ T-cells display a distinct gene expression profile relevant to multiple sclerosis. Issue 6 (27th May 2022) - Hrastelj, James; Andrews, Robert; Loveless, Samantha; Morgan, Joanne; Bishop, Mark; Bray, Nicholas; Williams, Nigel; Robertson, Neil
Abstract : Background: This study reports the largest transcriptomic analysis of purified CSF cell subpopulations to date. This has relevance for understanding CNS immune surveillance and multiple sclerosis pathogenesis and treatment discovery. Methods: CD4+ T-cells were purified from CSF and blood using fluorescence-activated cell sorting, from 21 patients with treatment-naïve multiple sclerosis and 20 individuals with non-inflammatory disorders. Their transcriptomes were profiled through RNA sequencing. A paired comparison was performed between CSF and blood within individuals. A further case-control comparison was performed in an extended cohort of CSF samples. Results: Paired comparisons between CD4+ T-cells from CSF and blood identified 5, 156 differentially expressed genes in controls and 4, 263 differentially expressed in multiple sclerosis patients at false discovery rate (FDR) < 5%. Differential expression analysis of CSF CD4+ T-cells highlighted genes involved in; migration, activation, cholesterol biosynthesis and signalling, including those relevant to multiple sclerosis patho- genesis and treatment. In an extended cohort of multiple sclerosis cases (N=41), analysis of CSF CD4+ T-cells compared with non-inflammatory disorder controls (N = 38) identified 140 differentially expressed genes at FDR < 5%. Conclusion: We report numerous gene expression differences between CSF and blood CD4+ T-cells. Identi- fied genes have relevance to multiple sclerosis pathogenesis and could contain novel treatment targets. james.hrastelj@gmail.com